2019
DOI: 10.1016/j.ecotra.2018.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Agglomeration, productivity and the role of transport system improvements

Abstract: We explore how the transport improvements impact agglomeration and thereby productivity in mid-Sweden including Stockholm 1995-2006. We measure agglomeration, and changes in agglomeration in response to transport improvements, based on travel times. This is a more accurate measure of agglomeration than previously used and also necessary for understanding how governments can impact agglomeration, and thereby productivity, by transport investments. We regress temporal changes in wages on temporal changes in aggl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 80 publications
(78 reference statements)
1
15
0
Order By: Relevance
“…In the aspect of land use development, it is well known that urban mass transit, such as light rail, Bus Rapid Transit (BRT), and metro, will increase the value of land use along the transit line [36,37]. Some researchers focus on the commercial investment based on the location of metro stations and land use [38][39][40][41]. Jian [42] studied the relationship of land use and metro passenger flow within a 500 m radius around the metro station in Osaka, Japan, and found that urban commercial building tends to be more dense when its location is closer to the metro station.…”
Section: Of 23mentioning
confidence: 99%
“…In the aspect of land use development, it is well known that urban mass transit, such as light rail, Bus Rapid Transit (BRT), and metro, will increase the value of land use along the transit line [36,37]. Some researchers focus on the commercial investment based on the location of metro stations and land use [38][39][40][41]. Jian [42] studied the relationship of land use and metro passenger flow within a 500 m radius around the metro station in Osaka, Japan, and found that urban commercial building tends to be more dense when its location is closer to the metro station.…”
Section: Of 23mentioning
confidence: 99%
“…Also, it seems that transit accessibility to jobs plays a key role toward increasing productivity (not analyzed in this paper). Recent publications suggest there is a positive and strong relationship between transport investment and GDP, and that accessibility is also positive related to wage earnings (Alotaibi, Quddus, & Imprialou, 2019;Börjesson, Isacsson, Andersson, & Anderstig, 2019). This suggests what probably matter most for productivity from a morphological point of view is not the geographical place (distance to center, etc.…”
Section: What We Know So Far About Urban Form (Spatial Structure) Andmentioning
confidence: 99%
“…Furthermore, effects differ between countries, time, industries, and modes of transport, explaining the wide range of estimates found in individual studies. Recent analyses accounting for the identified shortfalls fall into a more narrow range of estimates while providing evidence for many parts of the world: Besides others, Barzin, D'Costa, & Graham (2018) identify the impact of Colombian roads, L. Liu & Zhang (2018) study the high speed rail construction in China, and Arbués, Baños, & Mayor (2015) in Spain as well as Börjesson, Isacsson, Andersson, & Anderstig (2019) in Sweden focus on European countries. All authors find positive effects on production output and employment, as do several studies for the German case: The reports by Bertenrath, Thöne, & Walther (2006) and Barabas et al (2010) provide extensive background information as well as estimation results that are close to the findings of the mentioned meta-analyses.…”
Section: Literature Reviewmentioning
confidence: 99%